PARASITIC METAZOA OF TRIPORTHEUS ANGULATUS (SPIX & AGASSIZ, 1829) “SARDINA” ACQUIRED IN THE “BELÉN” IQUITOS MARKET, PERU - Rengifo-Chota, Heber David (2022)
Parasitic metazoans were determined in Triportheus angulatus (Spix & Agassiz, 1829) acquired from the "Belén" market in Iquitos, Peru. Thirty individuals of T. angulatus were collected, of which the gills, muscles and digestive tract were analyzed to find parasitic metazoans. The groups of identified parasites were Monogenoidea and Nematoda. Permanent slides cleared in Hoyer's medium were prepared for monogenoids for their identification. In nematodes, semi-permanent slides cleared with lactic acid were prepared. Parasitological indices were calculated for prevalence, intensity, mean intensity and mean abundance. One hundred fifty-one metazoan parasites were collected from T. angulatus acquired from the “Belén” market in Iquitos, Peru. The following monogenoids were identified: Anacanthorus acuminatus Kritsky, Boeger & Van Every, 1992; Anacanthorus chaunophallus Kritsky, Boeger & Van Every, 1992; Anacanthorus Chelophorus Kritsky, Boeger & Van Every, 1992; Anacanthorus euryphallus Kritsky, Boeger & Van Every, 1992; Anacanthorus lygophallus Kritsky, Boeger & Van Every, 1992; Anacanthorus pithophallus Kritsky, Boeger & Van Every, 1992; Ancistrohaptor falciferum Agarwal & Kritsky, 1998; Ancistrohaptor falcunculum Agarwal & Kritsky, 1998, three unidentified species belonging to the genus Jainus: Jainus sp1, Jainus sp2, Jainus sp3; and one species of Nematoda, Procamallanus (Spirocamallanus) inopinatus Travassos, Artigas et Pereira, 1928. The species belonging to nematoda presented the highest prevalence with 53.33% and an average abundance of 1.83 larvae on average. The genus Jainus sp3, presented the highest average intensity of 4.50. Keywords: monogenoids – nematodes – sardine – taxonomy